Effect of Addition Water Clover (Marsilea crenata) Extract in Tris-Egg Yolk Extender on Semen Quality of Kaligesing Goat - Windayanti, Aridha Elfarikha; Hariani, Dyah (LenteraBio : Berkala Ilmiah Biologi, 2023)
Fresh semen of Kaligesing goats cannot be stored for a long time at room temperature, it needs to be stored at freezing temperature so spermatozoa can survive for a long time. Egg yolk tris (TKT) diluent is needed with additional antioxidant to protect spermatozoa from free radicals. This study was aimed to determine the effect of water clover extract (ESA) addition in TKT on the quality of frozen semen of Kaligesing goats. This study used a completely randomized design with 4 concentrations of ESA (0%, 2%, 4%, 6%) in TKT with 5 repetitions. The evaluated quality of spermatozoa included motility, viability, and spermatozoa cell membrane integrity. Spermatozoa quality data were tested using Anava. If the results were significant, testing was continued with Duncan’s test. The results showed a significant effect of the administration of ESA on the quality of spermatozoa (P<0.05). ESA at 2% concentration resulted in the best result with motility of 38.50 ± 2.87, viability 47.46 ± 4.74, and cell membrane integrity 45.23 ± 3.43. The conclusion was the addition of 2% ESA in TKT diluent was the best concentration in maintaining the quality of frozen semen Kaligesing goats.